Presence of 2',5'-Bis-O-(tert-butyldimethylsilyl)-3'-spiro-5"-(4"-amino-1",2"-oxath iole-2",2"-dioxide) (TSAO)-resistant virus strains in TSAO-inexperienced HIV patients. - Van Laethem, K; Schmit, J; Pelemans, H; Balzarini, J; Witvrouw, M; Pérez-Pérez, M; Camarasa, M; Esnouf, R; Aquaro, S; Cenci, A; Perno, C; Hermans, P; et al. (2000)
HIV-1 samples from six patients undergoing diverse anti-HIV therapies possessed the E138A mutation in their reverse transcriptase (RT) genome. Patients were receiving the following therapies: TIBO monotherapy (one patient); zidovudine plus didanosine combination therapy (one); zidovudine monotherapy (one); sequential therapy with zidovudine, then stavudine and finally zalcitabine plus didanosine (one); and two were drug naive. E138K, not E138A, is a known TSAO-specific resistance mutation, emerging under selective pressure in vitro. Our phenotypic data on the patient isolates, confirmed by data on an E138A mutant acquired through in vitro mutagenesis, indicated that an alanine substitution for glutamate at codon 138 of the HIV-1 RT renders the virus TSAO resistant, confirming the importance of this amino acid residue in the activity of TSAO derivatives. In addition, we have demonstrated through phenotypic analysis of the E138A and A98S mutants (after in vitro mutagenesis) that the mutation A98S, found in one of these patients, could be partially responsible for the phenotypic reversal of TSAO resistance. This reversal could be explained by the restoration of a hydrogen bond between 98S and the main-chain residue L349, which compensates for the loss of the E138-G99 main-chain hydrogen bond. As TSAO derivatives have not been used in the clinical setting, the presence of the E138A mutation at a frequency of 6.7% in our study of 90 TSAO-inexperienced HIV-seropositive individuals implies that 138A of the RT must be a natural variant and that the mutant virus is replication competent. Our observations suggest that the E138A mutation may likely arise in patients under the selective pressure of TSAO or related compounds that show a decreased antiviral potency toward the E138A variant.